Types of Food to Promote the Activities Gastronomy Tourism in the Western Region - Chidprasert, Chonchanok; Tangtenglam, Susaraporn; Saesow, Chearnkwan; Pongpanic, Ariya; Sonthanong, Manasin (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
Due to the current state of tourism that comes from the trend of changing tourist behavior tourists combined with the trend of creative tourism found that tourists who travel to Thailand, there is still interested in trying local food to gain an appreciation of the culture. And with food tourism as an approach that opens opportunities for tourists to come in and experience and learn the culture as well the popularity of local food is culturally rooted and adapted for tourism in Characteristics of food culture are made into tourism products. (Commodification of Local Food), such as the Michelin Guide Thailand ranking To recommend restaurants for those traveling to Bangkok, Chiang Mai, Phuket, Phang Nga, and other cities to reflect their distinct identity and diversity. Of food culture and Thai tourism. This paper aimed to study Types of Food to Promote Activities of Gastronomy Tourism In the western region of Thailand with the quantitative method, the questionnaire covered 400 samples of Thai Tourists in Western Region Gastronomy Tourism In the western region of Thailand with non-probability and accidental sampling. Then, the data were analyzed with descriptive statistics for the respondent’s information and with the correlation and multiple regressions to find out any concordances between the Types of Food and Activities Gastronomy Tourism In the western region of Thailand. The research indicated that Types of Food to Promote Activities Gastronomy Tourism In the western region affected the success of Activities Gastronomy Tourism. The Types of Food to Promote Activities Gastronomy Tourism In the western region of Thailand as a whole were Types of Food (β = 0.325, α <.01) and Activities Gastronomy Tourism (β = 0.417, α <.05) with a statistically significant effect, respectively. They could jointly describe the variance of the Types of Food to Promote Activities Gastronomy Tourism In the western region of Thailand by 72.1% (R2 = 0.721) and the forecasting equations for the Types of Food to Promote Activities Gastronomy Tourism In the western region of Thailand. Among Thailand on the whole in standardized form was Zy = 0.325Z+0.417. Results of analysis of Types of Food to Promote Activities Gastronomy Tourism In the western region Thailand increased income from other channels.